Anatomia funcional do tubo digestivo de Gymnotus carapo Linnaeus, 1758 (siluriformes, gymnotoidei, gymnotidae) - Menin, Eliane (Revista Ceres, 2025)
The functional anatomy of the alimentary tract of Gymnotus carapo, a carnivorous fish, was examined. The digestive tract of this fish is constituted of eso- phagus, stomach, middle intestine and rectum; pyloric caeca are atached to the middle intestine. The viscerae are localized in the cranial portion of the coelomatic cavity and the rectum ends at the anus, near the isthmus region. The relatively long and very distensible esophagus conducts the food to the short caecal stomach and assists its storage there. The pyloric and ileocoecal constrictions, as well as the ileocoecal valve, control the passage of food through the digestive tract. Mucous folds and pyloric caeca increase the effective area of the middle intestine. The complexity of the mucosa at the caudal portion of the middle intestine and rectum suggests that absorptive processes predominate in this region. The average value of the intestinal coefficient (0,3) is practically constant for all body size classes indicating that the growth of the middle intestine and rectum, in this species,is proportional to the growth of the body and that there are no significant changes of diet.